The potential of Melaka traditional Malay houses as cultural heritage tourism product in Merlimau / Muhammad Asyrik Ismail - Muhammad Asyrik Ismail (2013)
Instead of becoming shelters of the people who live in, the Melaka traditional Malay houses reflect the owners’ social structure, traditions, history and culture livelihood of Merlimau. The houses are recognized as an authentic and unique architectural legacy of the Malays in peninsular Malaysia where most of them still maintaining the authenticity based on the original structure during the colonial era of the Dutch and British. The houses concerned were constructed based on history, socioeconomic and geography of the Merlimau area. This paper reports the potential of the houses as cultural heritage tourism products in Merlimau with regard to the authenticity or unique features as well as the experience of the tourists that will lead to the intention to revisit in the future. The result revealed that, destination attributes of authenticity or unique features of the houses have significant influence towards the tourist experience and will stimulate the intention to revisit. The trends of building modern and concrete houses will affect the original structure of the traditional houses or it will result them to be demolished. Therefore, adaptation and transformation of the houses as tourism products is an effective strategy to improve the sustainability of cultural and historical heritage for future generation.